Theory and practice of rapid and safe thermal debinding in ceramic injection molding. Issue 3 (30th August 2019) - Xie, Hehan; Jiang, Jie; Yang, Xianfeng; He, Qinglong; Zhou, Zhe; Xu, Xiewen; Zhang, Li
Abstract: In this paper, the dynamic process of thermal debinding was analyzed. The critical thickness of debinding was defined as the thickness at which the steps to control dynamics change from diffusion of gas products in liquid binder to diffusion or permeation in pores. Subsequently, the equation of critical thickness was deduced. The results show that the critical thickness of debinding is independent of the thickness of the green body, but mainly depends on the particle size, solid content, and binder composition. Moreover, larger particle diameter and higher solid loading will contribute to a greater critical thickness, which means that higher heating rate can be used in the initial stage of debinding. The prediction is in agreement with the experimental results. In addition, the effect of binder composition on the formation of cracks during thermal debinding was investigated by thermogravimetry combined with FTIR spectrometry (TG‐FTIR) analysis of binders and thermogravimetric curves of feedstocks. It suggests that the feedstock containing polystyrene and acrylic resin is helpful for rapid and safe thermal debinding.